Tumor protein D52 (TPD52) affects cancer cell metabolism by negatively regulating AMPK - Yali Chen; Changmin Peng; Wei Tan; Jia Yu; Jacqueline Zayas; Yihan Peng; Zhenkun Lou; Huadong Pei; Liewei Wang (Cancer Medicine, 2023)
Abstract Background The AMP‐activated protein kinase (AMPK) is a central regulator of energy homeostasis, with deregulation leading to cancer and other diseases. However, how this pathway is dysregulated in cancer has not been well clarified. Methods Using a tandem affinity purification/mass‐spec technique and biochemical analyses, we identified tumor protein D52 (TPD52) as an AMPKα‐interacting molecule. To explore the biological effects of TPD52 in cancers, we conducted biochemical and metabolic assays in vitro and in vivo with cancer cells and TPD52 transgenic mice. Finally, we assessed the clinical significance of TPD52 expression in breast cancer patients using bioinformatics techniques. Results TPD52, initially identified to be overexpressed in many human cancers, was found to form a stable complex with AMPK in cancer cells. TPD52 directly interacts with AMPKα and inhibits AMPKα kinase activity in vitro and in vivo. In TPD52 transgenic mice, overexpression of TPD52 leads to AMPK inhibition and multiple metabolic defects. Clinically, high TPD52 expression predicts poor survival of breast cancer patients. Conclusion The ﬁndings revealed that TPD52 is a novel regulator of energy stress‐induced AMPK activation and cell metabolism. These results shed new light on AMPK regulation and understanding of the etiology of cancers with TPD52 overexpression.